2011
DOI: 10.1016/j.ajpath.2011.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Progression of Prostate Cancer and E-Cadherin

Abstract: Expression of E-cadherin is used to monitor the epithelial phenotype, and its loss is suggestive of epithelial-mesenchymal transition (EMT). EMT triggers tumor metastasis. Exit from EMT is marked by increased E-cadherin expression and is considered necessary for tumor growth at sites of metastasis; however, the mechanisms associated with exit from EMT are poorly understood. Herein are analyzed 185 prostate cancer metastases, with significantly higher E-cadherin expression in bone than in lymph node and soft ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
119
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 58 publications
12
119
0
3
Order By: Relevance
“…Interestingly, however, we observed that Snai1 is expressed in the nucleus of mammary epithelial cells, but it does not repress ␤4 transcription. This observation is consistent with other reports of Snai1 expression in epithelial cells (16)(17)(18). Aside from the possibility that Snai1 can be excluded from the nucleus (19), it is not known why nuclear Snai1 does not repress genes in epithelial cells.…”
supporting
confidence: 82%
“…Interestingly, however, we observed that Snai1 is expressed in the nucleus of mammary epithelial cells, but it does not repress ␤4 transcription. This observation is consistent with other reports of Snai1 expression in epithelial cells (16)(17)(18). Aside from the possibility that Snai1 can be excluded from the nucleus (19), it is not known why nuclear Snai1 does not repress genes in epithelial cells.…”
supporting
confidence: 82%
“…Similarly, maintenance of E-cadherin expression is not detrimental to invasion and metastasis. Maintenance of E-cadherin expression in highly metastatic cell lines has been described in a number of preclinical models of metastasis of breast (4T1), prostate (DU145), and bladder (TSU-Pr1) cancers [40][41][42]. In this study, we examined the down-regulation of E-cadherin in MDA-treated 4T-1 cells and tumor tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Although WT1 has been proposed to regulate EMT by repressing E-cadherin; more recently, WT1 has been linked to the regulation of epicardial EMT through the β-catenin and retinoic acid signaling pathways (29). Interestingly, it has been found that WT1 transcriptionally activates Snail with partial maintenance of E-cadherin, and WT1 is associated with epithelial characteristics in kidney cells and in clear cell renal cell carcinoma (31). Thus, in these examples, WT1 induces an epithelial-mesenchymal hybrid transition defined by Snail upregulation with E-cadherin maintenance, a tumor cell differentiation state in which cancer cells retain both mesenchymal and epithelial features that may contribute to tumor cell plasticity and tumor progression (30).…”
Section: Developmental Expression Of Wt1mentioning
confidence: 99%
“…Thus, in these examples, WT1 induces an epithelial-mesenchymal hybrid transition defined by Snail upregulation with E-cadherin maintenance, a tumor cell differentiation state in which cancer cells retain both mesenchymal and epithelial features that may contribute to tumor cell plasticity and tumor progression (30). Similarly in prostate cancer (PC), a partial EMT with features of both epithelial and mesenchymal cells has been observed (31). The transformation of metanephric mesenchyme to epithelial cells within the condensing glomeruli also is similar to the metastatic process of cancer cells, whereby motile cancer cells, after extravasation, must revert back to their epithelial state to survive at the metastatic site (32).…”
Section: Developmental Expression Of Wt1mentioning
confidence: 99%